(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Through this study, the researcher aims to define the negative effects that the public’s exposure to the media coverage of news related to (COVID-19) can produce. The researcher depends on the functional approach, which indicates that the media provide its audience with a number of cognitive functions, and at the same time, cause a dysfunction, represented by some negative effects on the audience. The researcher adopted the survey method, with a study sample consisted of (175 respondents) of the Syrian public, at different demographic levels of (gender, age, education). The study reached a set of results, the most important of which are: The predominance of the average use of media and communication, during the period of the COVID-19 pandemic, among the sample. The digital media and communication exceeded over the traditional media, and the phrase (It gives me instructions on how to avoid infection with this pandemic), came first among the phrases of the cognitive functions. With regard to the negative effects (dysfunction), the phrase (I fear for my family from being infected by this pandemic), exceeded all the phrases. As for the results of the hypothesis test: it has been proven that there is a statistically significant correlation between the volume of the Syrian public’s use of media and communication, and both variables: the cognitive functions, and the dysfunction resulting from the use.